SUPERCRITICAL FLUID EXTRACTION OF TEBUPIRIMPHOS RESIDUES IN SUGAR BEET - BEET M. Pucarevi V; . Bursi; D. Pankovi R; . M. Nebojaa; M. Cara; I. Kecojevi (Journal of Animal and Plant Sciences, 2013)
Tebupirimphos or phostebupirim is an organophosphorous type insecticide (OP). A method for the determination of tebupirimphos residues in sugarbeet was developed. The tebupirimphos was extracted from the samples using supercritical fluid extraction (SFE) and analyzed by capillary gas chromatography coupled with nitrogen-phosphorus detection. The LOD of tebupirimphos was 0.0001 mg/kg, with the LOQ of 0.0003 mg/kg. In addition, the intra- and inter-day precision was satisfactory with RSD less than 10.0 %. Good detector response linearity (R2= 0.9914) was observed in the range of 0.00488-0.975 μg/ml. The recovery of supercritical extraction was 95.08 %, (RSD 8.2 %). It can be concluded that the tebupirimphos can be efficiently extracted using SFE and residues in the sugar beet root are present for a short time after the soil treatment with this insecticide.The resiudes of tebumpiriphos were no more present at harvest time.
Keywords: Supercritical fluid extraction; Residues; Tebupirimphos; Sugarbeet